2013
DOI: 10.1111/irv.12179
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A virus survival in water is influenced by the origin species of the host cell

Abstract: BackgroundInfluenza A viruses have an envelope made of a lipid bilayer and two surface glycoproteins, the hemagglutinin and the neuraminidase. The structure of the virus is directly dependent on the genetic makeup of the viral genome except the glycosylation moieties and the composition of the lipid bilayer. They both depend on the host cell and are in direct contact with the environment, such as air or water. Virus survival is important for virus transmission from contaminated waters in the case of wild aquat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 31 publications
(62 reference statements)
1
30
0
Order By: Relevance
“…85 A mechanistic understanding of this difference in susceptibility is unknown. 89 Based on the cumulative survivability data, it is plausible that an enveloped virus excreted in human feces or urine could survive in aqueous environments for periods of time that are relevant to the wastewater and drinking water treatment fields. 89 Based on the cumulative survivability data, it is plausible that an enveloped virus excreted in human feces or urine could survive in aqueous environments for periods of time that are relevant to the wastewater and drinking water treatment fields.…”
Section: Survival In Municipal Wastewatermentioning
confidence: 99%
“…85 A mechanistic understanding of this difference in susceptibility is unknown. 89 Based on the cumulative survivability data, it is plausible that an enveloped virus excreted in human feces or urine could survive in aqueous environments for periods of time that are relevant to the wastewater and drinking water treatment fields. 89 Based on the cumulative survivability data, it is plausible that an enveloped virus excreted in human feces or urine could survive in aqueous environments for periods of time that are relevant to the wastewater and drinking water treatment fields.…”
Section: Survival In Municipal Wastewatermentioning
confidence: 99%
“…The swine and human viruses included in this study, however, demonstrated greater persistence at low temperatures than did a suite of viruses of avian origin that were previously analyzed (12). This result may be an artifact of how the human and swine viruses tested in our study were propagated; it has been shown that both human and avian viruses grown on MDCK cells are more stable at higher temperatures than are the same viruses when grown in chicken eggs (24). At higher temperatures, all the viruses assessed, regardless of their subtype and origin, were quickly inactivated, especially at temperatures higher than 28°C; this is similar to the reduction in persistence seen for a 2009 pandemic H1N1 and a 1999 seasonal H1N1 from Ͼ150 days at 4°C to just 2 days at 35°C (22).…”
Section: Discussionmentioning
confidence: 67%
“…The limit of quantification, and possibly the limit of detection, should be reported to analyze inactivation curves. In the case of the evaluation of a factor's impact, it may be useful, for interstudy comparison purposes, to include a standardized, controlled medium as a reference; for example, distilled, demineralized, sterile water could be included in parallel with the medium of interest [21,22,49]. Precise knowledge of factors influencing virus survival should be available by reporting not only the varying factors of the experimental design, but also the surrounding conditions, such as illumination, aeration, and microbial concentration, etc.…”
Section: Discussionmentioning
confidence: 99%
“…If viruses are able to survive freezing temperatures, ice may offer them protection from the environment, such as a reduced penetration of UV. The nature of the envelope, which comes from the cellular host of the virus, also plays a role in their survival: influenza viruses released from mammalian cells were shown to have significantly higher survival in water at 35 ° C than viruses released from avian cells [49].…”
Section: Mechanisms Of Virus Resistancementioning
confidence: 99%